PENGARUH LATIHAN PASSING BAWAH BERPASANGAN TERHADAP KETEPATAN PASSING BAWAH PADA TIM BOLA VOLI PUTRI SULTANIKA MINAS - Ainil Hayat Kusman; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The background of this research is training when passing down with incorrect technique, so that when passing down it does not get maximum results such as passing not to friendship and riding the ball when passing too low cannot be processed by the toser or feeder. This research was conducted in the Chevron field at Jalan Yossudarso KM 13, Minas District and was conducted in January to July 2019. The population in this study was less than 100 (only 10 people), so the sample in this study was 10 people, so the research was research research. To collect the data needed in this study, the Brumbach Test instrument arm passed the wall-volly test "passes down into the wall in the pre-test and post-test. Based on the analysis carried out, the value of t-counts between the initial test and the final test of the Paired Lower Passing to the accuracy of passing under the table at a significant level of 0.05 with degrees of freedom N - 1 (10-1 = 9). This shows the value of tcount (9.23)> ttable (1.833). Therefore, it can be concluded that the hypothesis referred to in the Under pairing Passing exercise (X) to the accuracy (Y) of Sultanika Minas women's volleyball team.Key Words: Underpass Passing Exercises In Pairs, Under Passing Accuracy